Legal norms and normativity : an essay in genealogy - Delacroix, Sylvie (Legal theory today., 2006)
This book offers a 'genealogical' explanation of law's normativity. The term 'genealogical' conveys a commitment to a non-metaphysical type of enquiry. While it explains how law, as a normative phenomenon, comes about, it does not seek to ground law's normativity in anything but the context of social interaction giving rise to it. Legal normativity is brought about on a daily basis. Whether in revolutionary circumstances or in the quotidian need for judges, lawmakers or citizens to balance law's demands with those of morality or prudence, our ability to bind ourselves through law ultimately.